Machine perfusion versus cold storage for the preservation of kidneys donated after cardiac death: a multicenter, randomized, controlled trial. - Jochmans, I; Moers, C; Smits, J; Leuvenink, H; Treckmann, J; Paul, A; Rahmel, A; Squifflet, J; van Heurn, E; Monbaliu, D; Ploeg, R; Pirenne, J (2010)
OBJECTIVE: Hypothermic machine perfusion may improve outcome after transplantation of kidneys donated after cardiac death (DCD), but no sufficiently powered prospective studies have been reported. Because organ shortage has led to an increased use of DCD kidneys, we aimed to compare hypothermic machine perfusion with the current standard of static cold storage preservation. METHODS: Eighty-two kidney pairs from consecutive, controlled DCD donors 16 years or older were included in this randomized controlled trial in Eurotransplant. One kidney was randomly assigned to machine perfusion and the contralateral kidney to static cold storage according to computer-generated lists created by the permuted block method. Kidneys were allocated according to standard rules, with concealment of the preservation method. Primary endpoint was delayed graft function (DGF), defined as dialysis requirement in the first week after transplantation. All 164 recipients were followed until 1 year after transplantation. RESULTS: Machine perfusion reduced the incidence of DGF from 69.5% to 53.7% (adjusted odds ratio: 0.43; 95% confidence interval 0.20-0.89; P = 0.025). DGF was 4 days shorter in recipients of machine-perfused kidneys (P = 0.082). Machine-perfused kidneys had a higher creatinine clearance up to 1 month after transplantation (P = 0.027). One-year graft and patient survival was similar in both groups (93.9% vs 95.1%). CONCLUSIONS: Hypothermic machine perfusion was associated with a reduced risk of DGF and better early graft function up to 1 month after transplantation. Routine preservation of DCD kidneys by hypothermic machine perfusion is therefore advisable.